2004
DOI: 10.7748/nr2004.07.11.4.79.c6217
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve: the advantages and disadvantages in the use of focus groups as a method of data collection

Abstract: Focus groups are not simply a discussion between people, but are focused interviews exploring interactions between participants. In this paper, Ian Mansell, Glynis Bennett, Ruth Northway, Donna Mead and Laurie Moseley explore the complexities and practicalities of using focus groups in research, with reference to a study of palliative care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 0 publications
0
79
0
6
Order By: Relevance
“…The transcripts were copied for the group so that members could read it and validate what had been recorded. The question of participants validating transcripts did cause the researcher some concern as it has been reported that there is a risk that people will remember what they wished they had said or what they thought they had said, rather than what they had actually said (Mansell et al, 2004). However, in this study there was no need for concern as the participants validated what was recorded.…”
Section: The Analysis Processmentioning
confidence: 89%
“…The transcripts were copied for the group so that members could read it and validate what had been recorded. The question of participants validating transcripts did cause the researcher some concern as it has been reported that there is a risk that people will remember what they wished they had said or what they thought they had said, rather than what they had actually said (Mansell et al, 2004). However, in this study there was no need for concern as the participants validated what was recorded.…”
Section: The Analysis Processmentioning
confidence: 89%
“…The aim of the focus group discussions was for participants to explore and indicate their level of agreement that a given criterion on the interview schedule suggests that the NPO is doing the right thing. Mansell, Bennett, Northway, Mead, and Moseley [29] argue that differences in management levels among members of a focus group lead to hierarchical differences, which not only intimidate but also make some members uncomfortable to provide information. To prevent such a situation from occurring, Mansell et al [29] suggest that less senior members can become moderators and assistant moderators of the focus group discussion.…”
Section: Interviews With Managementmentioning
confidence: 99%
“…Mansell, Bennett, Northway, Mead, and Moseley [29] argue that differences in management levels among members of a focus group lead to hierarchical differences, which not only intimidate but also make some members uncomfortable to provide information. To prevent such a situation from occurring, Mansell et al [29] suggest that less senior members can become moderators and assistant moderators of the focus group discussion. This technique was used with the consent of the Director who committed to ensuring that all the members freely participated at the same level.…”
Section: Interviews With Managementmentioning
confidence: 99%
“…In the focus group interviews, some participants can become dominating, thus making other participants say very little (Mansell, Bennett, Northway, Mead, & Moseley, 2004). In the CW, there is room for all the participants to give their input because they have already written it on the paper notes, which therefore become a way for them to engage in the discussion.…”
Section: The Chronicle Workhop -Theoretical Backgroundmentioning
confidence: 99%